Perancangan Sistem Pendukung Keputusan Pembagian Harta Waris Dalam Islam Berbasis Web Menggunakan PHP Dan MySQL - Dedi, Dedi; Iqbal, Muchamad; Yasin, Muhammad (JURNAL SISFOTEK GLOBAL, 2014)
The division of the inheritance are often the things that trigger conflict and cause family rifts. Faraidh is ensuring that one’s assets are shared among the benefactors without rancor. Designing an application of web-based calculation of the inheritance today is a necessity that can cover the weaknesses in desktop applications. Through a web-based software that is expected of the Muslims do not face obstacles in implementing the Islamic law, division of the inheritance is no exception because almost all the people who can use a computer can open a web page without the need to install first. Designed using expert system development methodology of John Durkin in building the knowledge base in the form of rules which are used in the determination of the proportion for heirs. As in software engineering using Rational Unified proccess methodologies using UML as a tool in the design of the system. The end product of this inheritance decision support system provides facilities such as the page that contains the definition of inheritance, arguments of inheritance, the heirs and their parts and the conditions, problems in Islamic inheritance, and program division of inheritance. Division of inheritance by the system is divided to four steps, the first one asked is the amount of treasure, both will ask the rights that must be met, the third will be asked to heirs, and the fourth displays the results of the calculations are in accordance with the rules of the Islamic inheritance.